2020
DOI: 10.48550/arxiv.2005.09237
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acoustic Echo Cancellation by Combining Adaptive Digital Filter and Recurrent Neural Network

Lu Ma,
Hua Huang,
Pei Zhao
et al.

Abstract: Acoustic Echo Cancellation (AEC) plays a key role in voice interaction. Due to the explicit mathematical principle and intelligent nature to accommodate conditions, adaptive filters with different types of implementations are always used for AEC, giving considerable performance. However, there would be some kinds of residual echo in the results, including linear residue introduced by mismatching between estimation and the reality and non-linear residue mostly caused by non-linear components on the audio device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…With the advent of deep learning techniques, several supervised learning algorithms for AEC have shown better performance compared to their classical counterparts [2,3,4]. Some studies have also shown good performance using a combination of classical and deep learning methods such as using adaptive filters and recurrent neural networks (RNNs) [4,5] AEC models, there has been no evidence of their performance on real-world datasets with speech recorded in diverse noise and reverberant environments. This makes it difficult for researchers in the industry to choose a good model that can perform well on a representative real-world dataset.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of deep learning techniques, several supervised learning algorithms for AEC have shown better performance compared to their classical counterparts [2,3,4]. Some studies have also shown good performance using a combination of classical and deep learning methods such as using adaptive filters and recurrent neural networks (RNNs) [4,5] AEC models, there has been no evidence of their performance on real-world datasets with speech recorded in diverse noise and reverberant environments. This makes it difficult for researchers in the industry to choose a good model that can perform well on a representative real-world dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Customized AEC adaptive filters take many forms including algorithms based on sparsity [6], adaptive normalization [7], and adaptive learning-rates [8], as well as data-driven approaches for selecting learning rates automatically [9,10] and based on a meta-stepsize [11,12]. More recently, deep learning techniques have been used as AEC sub-components including learned residual echo suppressors [13,14,15], double-talk detectors [16], and nonlinear distortions blocks [17,18,19,20,21]. These approaches, however, commonly do not use neural network modules that adapt at test In the machine learning literature, there have been exciting developments in meta-learning, automatic machine learning, and learning how to learn methods.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, numeric methods have been proposed, such as Nonlinear AEC (NLAEC) method where a set of nonlinear basis functions are used for AEC [9,10,11] and nonlinear post-filtering method where an additional nonlinear processing module is cascaded for residual echo suppression [12,13,14,15]. Recently, since its great potential in speech processing tasks, neural network (NN) has been used for AEC, such as NN-based post-filtering method where NN is used for residual echo suppression instead of conventional post-filters [16], NN-based NLAEC method where NN is used for modeling nonlinear echo [17], separation-based method where source separation with an additional information from the far-end [18] is used for AEC, NN-based adaptive filtering method where the structure of AF is adopted for designing AEC network [19,20].…”
Section: Introductionmentioning
confidence: 99%